The early phase of programmed cell death in Caco-2 intestinal cells exposed to PTH - Calvo, Natalia Graciela (2008)
The regulation of apoptosis is critical for ensuring the homeostasis of an organism. As such, the cell has derived various mechanisms to precisely control the balance between survival and apoptotic signaling. Parathyroid hormone (PTH) function as a major mediator of bone remodeling and as an essential regulator of calcium homeostasis. Depending on the cell type involved, PTH also inhibits or promotes the apoptosis. In a previous work we found that PTH promotes the apoptosis of human Caco-2 intestinal cells. In the current study, we demonstrate, for the first time, that stimulation of Caco-2 cells with PTH (10-8 M) results in the dephosphorylation and translocation of proapoptotic protein Bad from the cytosol to mitochondria and release of cytochrome c and Smac/Diablo. The hormone also triggers mitochondria cellular distribution to the perinuclear region, morphological features consistent with apoptosis. PTH increases the enzymatic activity of caspase-3 (48 h) that is also evidenced from the appearance of its cleaved fragments in western blot experiments. Moreover, active caspase-3 is present in nucleus after PTH treatment. In addition, a caspase-3 substrate, poly (ADP-ribose) polymerase (PARP), is degraded by 48 h of PTH treatment. Taken together, our results suggest that, in Caco-2 cells, the induction of apoptosis in response to PTH is mediated by translocation of mitochondria to the perinuclear region, dephosphorylation of Akt, dephosphorylation of Bad and its movement to the mitochondria and subsequent release of cytochrome c and Smac/Diablo which result in activation of downstream caspase-3.